Free standing 3D graphene nano-mesh synthesis by RF plasma CVD using non-synthetic precursor. (November 2015) - Ouyang, Bo; Jacob, Mohan V.; Rawat, R.S.
Graphical abstract: Schematics of the growth process of GNMs synthesized on a Ni substrate have been proposed. Highlights: 3D-Graphene nano-mesh (GNM) is synthesized with template-free approach. Environmentally-friendly non-synthetic precursor is used for fabricating 3D-GNM. 3D-GNM growth process in PECVD system has been outlined. As-synthesized 3D-GNMs are of high density and almost similar size and thickness. Abstract: Three dimensional graphene nano-mesh (3D-GNM) has been synthesized by radio frequency plasma-enhanced chemical vapor deposition. The 3D-GNM with various shapes is obtained on nickel foam substrate without using any nano-network as a pattern mask. Moreover, non-synthetic precursor Melaleuca alternifolia oil, with environmentally-friendly properties, is used as the carbon source for synthesis of 3D-GNM. This synthesis route with low energy expenses and little environmental contamination provides a simple and cost effective fabrication of 3D-GNM for utilization in future fundamental studies related to graphene.